Rehydration strategies--balancing substrate, fluid, and electrolyte provision - Murray, R. (International Journal of Sports Medicine, 1998)
The combination of heat stress, dehydration, and exercise imposes perhaps the most-severe physiological challenge for the human body short of disease or serious bleeding. Exercise in the heat requires the body to attempt to cope simultaneously with competing demands for cardiovascular homeostasis, thermoregulatory control, and maintenance of muscle energetics. When dehydration is superimposed upon this scenario (as is often the case during most forms of exercise), the results can be catastrophic for both health and performance. Fluid replacement reduces the risk of heat illness and improves exercise performance by preventing or reducing dehydration and by providing a convenient means of ingesting carbohydrate. The fact that even low levels of dehydration (e.g., equivalent to a 2% loss of body weight) impair cardiovascular and thermoregulatory response, and reduces the capacity for exercise, is beyond scientific dispute. For these reasons, optimal performance is possible only when dehydration is minimized by ingesting ample volumes of fluid during exercise. Recent research has demonstrated that consuming fluid in direct proportion to sweat loss (or close to it) maintains important physiological functions and significantly improves exercise performance, even during exercise lasting only one hour. Preventing dehydration enables the cardiovascular system to maintain blood pressure and cardiac output, thereby sustaining the increase in skin blood flow and sweating that are essential for optimal temperature regulation. Remaining well hydrated during exercise also preserves muscle function, reducing the reliance on muscle glycogen as a fuel source. Carbohydrate ingestion also improves exercise performance, an effect that is independent of and additive to preventing dehydration. The practical application of this knowledge requires that athletes follow a more-aggressive fluid-replacement regimen than is now usually the case. Successful implementation of this regimen requires that coaches, athletes, and support personnel are made aware of the practical benefits of adequate fluid replacement, that appropriate fluid-replacement strategies are developed and implemented, and that athletes have the opportunity to train themselves to ingest larger volumes of fluid more frequently. Success during competition in warm weather is more likely for those athletes who are highly fit and well acclimatized to training and competing in the heat, and who diligently avoid even low levels of dehydration. The competitive advantage will definitely shift in favor of those athletes whose coaches and trainers recognize the fundamental value of fitness, acclimation, and hydration, coupled with other strategies for keeping athletes cooled and fueled.